The Influence of Servant Leadership on Motivation and Job Satisfaction Employees at the Ministry of Religious Affairs of Merauke Regency: The Mediation Role of Trust in Leaders - Yohana Ramma; Shine Pintor S. Patiro; Anshar Daud (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the direct influence of servant leadership on trust in leaders, work motivation, and employee performance satisfaction. This study also examines the mediating role of trust in leaders in the influence of servant leadership on employee motivation and job satisfaction. This research is quantitative and uses a questionnaire research instrument to collect data. The sample of this study was 96 employees at the Office of the Ministry of Religious Affairs of Merauke Regency. The data analysis method used Structural Equation Modelling Partial Least Square (SEM-PLS). The results showed that servant leadership positively affects trust in leaders, work motivation, and employee performance satisfaction. In addition, trust in leaders is proven to mediate the relationship between servant leadership and work motivation. Trust in leaders is not proven to mediate the relationship between servant leadership and job satisfaction significantly. The findings contribute to the development of servant leadership theory and the importance of applying the servant leadership style in public sector organizations because it can increase employee trust, work motivation, and job satisfaction.